Students' performance in soil engineering course via active learning / Farah Wahida Mohd Latib, Noorul Iqhlima Najwa Ismail and Duratul Ain Tholibon - Mohd Latib, Farah Wahida; Ismail, Noorul Iqhlima Najwa; Tholibon, Duratul Ain (Universiti Teknologi MARA Cawangan Pahang, 2021)
Soil Engineering is one of the compulsory subjects taken by students pursuing a Diploma in Civil Engineering. This is an application subject where students need to have a good fundamental knowledge in Soil Mechanics in order for them to understand and apply the knowledge into real cases. However, the failure rate of Soil Engineering is quite high for every semester; 25-30% of the students taking this subject. Based on the results of a diagnostic test that was given early in the semester, most of the students obtained a C grade in Soil Mechanics; hence, various teaching and learning methods have been implemented to cater to Generation Z's way of learning. The active learning methods are project based learning, group discussions, site visits, 3D models and video making. The aims are to increase the fundamental knowledge of this course, enhance the cognitive and effective domains, help students apply the knowledge into real situations and to reduce the failure rate. As a result, after the three semesters of trying to meet the students' needs and subject requirements, the percentage score of more than 50% for PO2 was achieved.